THE DISCRETIONARY AUTHORITY OF STATE ADMINISTRATIVE OFFICIALS IN PUBLIC DECISION-MAKING RELATED TO LAW AND ETHICS: Kewenangan Diskresi Pejabat Administrasi Negara pada Pengambilan Keputusan Publik terkait Hukum dan Etika - Hendri Gunawan; Frinaldi Frinaldi; Roberia; Angga Putra Tri Rezeki (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2026)
Modern governance systems based on law place discretion as an important tool for state administrative officials, especially to ensure the continuity of public services in situations of legal vacuum or emergency. Previous studies have not comprehensively examined the relationship between legal basis, practical application, and ethical and accountability challenges in the use of discretion. This study aims to fill this gap by analysing the concept, legal basis, and implementation of discretion in Indonesian government administration.This study uses a normative legal research method with a legislative approach and is supported by a literature study from Google Scholar secondary data. The results show that although discretion has strong legal legitimacy, its implementation often causes irregularities due to weak oversight mechanisms and low ethical integrity among some public officials. The use of discretion without moral consideration and without upholding the principle of accountability has the potential to harm the interests of the community and reduce public trust.This study emphasises the importance of strengthening the integration between legal norms, ethical standards, and oversight systems so that the practice of discretion is in line with the values of justice, transparency, and responsible public service.